(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims to reveal the academic compatibility level among a sample of Tishreen University students and it’s relation to failure and success causes attribution and some demographic parameters . To achieve the research goals, the academic compatibility scale by (Bhdon Siryk) was used where this scale is translated and adapted to Egyptian environment by (Abd Al-Salam, 2002). This scale is composed of (36) clause that spread over 4 dimensions . In addition, the scale of casual attribution of failure and success reasons by Lefcurt and his friends, was used after modifying a sample was composed of (478) students of different scientific and literature colleges in Tishreen University. Some results are: - The level of academic compatibility among the sample members is medium, where all dimensions of the academic compatibility scale are of medium level except the dimension of " commitment to achieve goals " that is of low level. - The sample members attribute their success to internal reasons more than external ones. - Presence of relational connection of statistical reference between the level of academic compatibility and success and failure attribution reasons of member of the sample. - Absence of difference of statistical reference among the averages of research members response levels over the dimensions of academic compatibility and according to college parameter to the favour of literature college and according to the residence parameter in favour to Lattakia inhabitants .